2023
DOI: 10.3390/plants12010198
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of the Invasive Weed Solidago canadensis L. (goldenrod) and Copper Immobilization by a Community of Sulfate-Reducing and Methane-Producing Bacteria

Abstract: The weed Solidago canadensis L. poses a global threat to the environment as it spreads uncontrollably on roadsides, in forests, fields, meadows, and farmland. Goldenrod emits toxic substances that suppress other plants on the site, displacing wild ones. Thus, goldenrod conquers huge areas very quickly. The use of herbicides and mechanical methods does not solve the problem of the spontaneous spread of goldenrod. On the other hand, many scientists consider goldenrod as a valuable source of biologically active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Elsheikh et al [ 177 ] reported that IPS potentially alter the composition and diversity of the aboveground plant community structure. Havryliuk et al [ 178 ] reported that the invasive plant ( S. canadensis ) immobilized the Cu concentration with methane–sulfate-reducing bacteria with the help of phytodegradation. Usually, the viability of invasive exotic plants is influenced by soil microbial populations [ 179 ].…”
Section: Biotechnological Processes For Enhancing Phytoremediation Po...mentioning
confidence: 99%
“…Elsheikh et al [ 177 ] reported that IPS potentially alter the composition and diversity of the aboveground plant community structure. Havryliuk et al [ 178 ] reported that the invasive plant ( S. canadensis ) immobilized the Cu concentration with methane–sulfate-reducing bacteria with the help of phytodegradation. Usually, the viability of invasive exotic plants is influenced by soil microbial populations [ 179 ].…”
Section: Biotechnological Processes For Enhancing Phytoremediation Po...mentioning
confidence: 99%
“…However, it may still be insufficient compared to salt tolerance, broad substrates, and cold tolerance. Meanwhile, methanogens, as common archaea in the intertidal sediments of coastal wetlands with an extremely low relative abundance in this investigation, are extremely common in intertidal environments as the last link of carbon cycle degradation in anaerobic degradation environments [ 37 , 38 ]. This suggests that surface sediments may have been subjected to less direct inundation by seawater and rainfall, lacking an anaerobic environment.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered to be more environmentally friendly comparing to physical and chemical ones 5 . Bio-based methods are used for fuel obtaining [19][20][21][22] , treatment of soil and water from hazardous xenobiotics [23][24][25][26][27] , pathogens control 1,28-30 , etc.…”
Section: Discussionmentioning
confidence: 99%